A wideband CPW slot antenna by using conductor-backed coplanar feeding - Yulei Xue; Ruiqiang Yan; Weiping Huang; Yanchen Dong (Heliyon)
In this paper, a new wideband coplanar waveguide (CPW) rhomboid slot antenna by using conductor-backed coplanar waveguide (CBCPW) feeding, which works at 4.6 GHz with a relative impedance bandwidth of about 55.6 %, and a gain of more than 5.5dBi from 4 to 6 GHz, has been proposed, and the performance of a CPW circular slot antenna and a CPW rectangular slot antenna are also used for comparing with the proposed antenna. It is demonstrated that the CPW rhomboid slot antenna has wider impedance bandwidth, higher gain and better radiation pattern compared with the circular and rectangular slot antennas, meanwhile, low profile has also realized. The CPW rhomboid slot antenna with CBCPW feeding has been fabricated and measured, and the design has been verified.